Description of the Ministry of Educations proposals concerning the evaluation of intellectual disabilities - Veltrone, Aline Aparecida; Mendes, Enicéia Gonçalves (Paidéia (Ribeirão Preto), 2011)
This paper describes and examines the official recommendations of the Brazilian Ministry of Education (MEC) concerning the identification of intellectual disability in students. This study was conducted through the analysis of MECs legal and normative documents concerning assessment of intellectual disability. First, an analysis protocol was developed to address the following information: documents name, description and synthesis. The model of the analysis protocol was divided into three themes: definition of intellectual disability condition, assessment of intellectual disability condition, and educational support. The results reveal there is legal uncertainty concerning official guidelines on how to identify students with intellectual disabilities, whose consequences are still unknown.